Immunomodulatory Activity Of Mannheimia Haemolytica A2 Lipopolysaccharide - Mohd.Salim, Azlina (2003)
Bacterial lipopolysaccharides ( LPS) are endotoxins. However, there ample evidence to support its role in immunomodulation. In fact LPS is commonly used as a B cell mitogen. The activity of LPS from different genera of bacteria varies considerably which makes generalisation of characteristics difficult. Despite their lethal consequences, the LPS of Mannheimia haemolytica A2 have not been tested for immunomodulatory activity. Therefore, the objective of this study is to investigate the adjuvant properties of LPS from Mannheimia haemolytica A2 upon peripheral and mucosal immunity toward protein antigen. The experimental results indicate that, the group of mice that received 10 ug LPS in oil induced anti-BSA IgG response in serum and pulmonary antibody response when administered intraperitoneally. However, in the IgG and 1gA intestinal antibody response, mice received 10 ug LPS without oil showed significantly high compared to controls